Effect of chlorine on filamentous microorganisms present in activated sludge as evaluated by respirometry and INT-dehydrogenase activity - Caravelli, Alejandro Horacio (2004)
Activated sludge technology is more used than any other for biological treatment of wastewater. However, filamentous bulking is a very common problem in activated sludge plants, chlorine being the chemical agent normally used to control it. In this work the effect of chlorine on micro-organisms present in activated sludge flocs was assessed by a respirometric technique (oxygen uptake rate, OUR) and by the INT-dehydrogenase activity test (DHA) measured by two techniques: spectrophotometry (DHA a) and image analysis (DHA i). Both DHA tests were optimized and correlated with the respirometric technique (OUR) using pure cultures of a filamentous micro-organism (Sphaerotilus natans) under chlorine inhibition. Using these correlations the tested methods were applied to determine the action of chlorine on respiratory activity in activated sludge. The OUR and the DHA a quantifies the action of chlorine on the total respiratory activity (RA) of flocs (filamentous and floc-forming bacteria); in contrast, the DHA i test evaluates specific action of chlorine on the RA of filamentous micro-organisms. In activated sludge flocs containing filamentous microorganisms, a chlorine dose of 4.75 mgCl2 (gVSS)-1 with a contact time of 20 minutes reduced about 80% of the RA of filamentous bacteria while affecting only 50-60% of the total RA of flocs. Besides, a chlorine dose of 7.9 mgCl2 (gVSS)-1 produced the total respiratory inactivation of filamentous micro-organisms after 10 min contact, however, with this dose the total RA of activated sludge flocs was reduced only about 45-65%; controlling filamentous bulking without affecting too much floc-forming bacteria. At the tested chlorine concentrations the inhibition of filamentous micro-organisms was higher than in the whole activated sludge. Although floc-forming micro-organisms were demonstrated to be more susceptible to chlorine than filamentous in pure cultures, results obtained in the present work confirmed that it is the location of the filamentous micro-organisms in the flocs and the presence of extracellular polymers substances which largely determines their higher susceptibility to chlorine; consequently this feature plays a critical role in bulking control. Although floc-forming micro-organisms were demonstrated to be more susceptible to chlorine than filamentous in pure cultures, results obtained in the present work confirmed that it is the location of the filamentous micro-organisms in the flocs and the presence of extracellular polymers substances which largely determines their higher susceptibility to chlorine; consequently this feature plays a critical role in bulking control.